A internacionalização de empresas brasileiras e recrutamento de seus executivos: estudo de caso do grupo Gerdau - Julian, Erica Ambiel (2013)
The present research seeks to explore the influence of international studies inside companies, this study is about managers hiring for transnational companies. The globalization of Brazilian businessare driven by the desire ofnew markets and growth capital, motivate by some Brazilian companies that occupy space in the global scenario. This is a result of several factors that make easy the transition of knowledge and managerial, people and capital, creating an open world market, and to receive strong competitors who aspire to work globally with consumers and employees. The consequences for thisprocess described are diverse within the internal scenarios in each country, both for those countries that receive foreign capital,or for those countries that allow the entry of foreign products, and for those who seek new horizons. Professionals who hold positions within these organizations turn into an international model. Their executives modify the professional profile of the field, transforming the way of hiring their successors to meet international requirements. The arrival of foreign structures to local, and mainly local expertise, renews the perception that agents have on the field of disputes, best professional positions in the job market also propose changes in the type of trajectory and how they make choices for desire positions of importance. Thus, besides the economic and cultural aspects surrounding the circulation of companies, it is interesting to note the changes in the social environment and internal policy related. To better understand the phenomenon described, was used this research in the Metalúrgica Gerdau S.A., its employees and its history.